Dementia Symptoms among Senior Citizens Living in Geriatric Homes of Kathmandu Valley - Singh, D. R.; Parajuli, P.; Hug, J.; Nath, D.; Koirala, R.; Mandal, R. (Kathmandu University Medical Journal, 2021)
Background With increasing age, the older population becomes more susceptible to mental disorders. It is important to recognize and develop an understanding of psychiatric morbidity particularly among the residents of geriatric homes in resource-poor settings. Objective To assess the prevalence and associated factors of dementia symptoms among Nepalese senior citizens living in geriatric homes of Kathmandu valley. Method A cross-sectional study was conducted among 304 senior citizens living in geriatric homes of Kathmandu valley. Cognitive Impairment Test (CIT), was used to assess dementia symptoms. Bivariate and multivariate logistic regressions were performed. All the variables that were significant at p < 0.05 level in the bivariate analysis were included in the multivariate regression model and statistical significance was declared at p < 0.05 with a 95.00% confidence interval (CI). Result This study showed 75.65%, of the participants, had dementia symptoms. In the multivariate logistic regression analysis, female respondents (AOR=2.94, 95% CI=1.31-6.57), respondents never received geriatric allowances (AOR=2.46, 95% CI=1.22-4.98), respondent’s history of alcohol consumption habits (AOR=2.04, 95% CI=1.01-4.11) and non-vegetarian diet habits (AOR= 2.31, 95% CI=1.12-4.76) were found more likely to had higher dementia symptoms whereas, literate participants (AOR=0.19, 95% CI=0.08-0.43) were less likely to had dementia symptoms. Conclusion The high prevalence of dementia symptoms among senior citizens living in geriatric homes in the Kathmandu valley indicates an urgent need for early diagnosis and treatment of mental disorders among senior citizens to improve their quality of life and well-being.